ADMINISTRATIVE LEADERSHIP CONFLICTS AND CAUSES IN NIGERIA’S HEALTH SYSTEM - MICHAEL OKECHUKWU IHEONU; IRO IRO UKE (International Studies Journal)
Identification of the existence of conflicts, and evaluation of stakeholders’ opinions on the possible causative elements, are the main thrusts of this study. Survey research design was adopted on the informed populations of medical doctors, medical laboratory scientists, nurses, optometrists, pharmacists, physiotherapists and radiographers, practising in the six Area Councils of the Federal Capital Territory Abuja, Nigeria, using a stratified sample size of 1642. Primary data were opinions directly obtained from the respondents. Secondary data were from textbooks, journals and gazetted government documents. This study established that conflicts exist over Nigeria’s health system leadership, with the major causes being:non-respect of lawful professional boundaries, arrogance among professionals, unacceptability of foisted leaderships, and ambiguities in Government regulatory guidelines and Minor causes are: inferiority complex among certain professionals, inter-professional congestions in pursuing compatible goal of patients’ well-being, incompatibility of goals when professional interests are prioritised, scarcities of resources and positions. It is recommended that the respective curricular of health professions’ training schools, should be reviewed to inculcate discipline, conviviality and team-spirit in the out-going graduates. The continuing professional development programmes for practising professionals should be expanded to have inter-professional cross-fertilization of ideas, for better tolerance among health professionals.